The Impact of Pharmaceutical Care Services on Patients with Active Rheumatoid Arthritis: A Randomized Controlled Study - Hagar Elmenshawy; Hanan Farouk; Nagwa Sabri; Marwa Ahmed (Ain Shams University, 2022)
The objective of our study was to investigate the impact of pharmaceutical care services on the detection and resolution of drug-related problems (DRPs) in rheumatoid arthritis (RA) patients. It was a randomized controlled study in which 60 eligible patients were recruited and randomly assigned to either an intervention (N = 30) or a control group (N = 30). The intervention group received pharmaceutical care services including management of drug-related problems (DRPs) in addition to standard care. Patients in the control group received only the standard care. Both groups were evaluated for DRPs, disease activity, functional disability, adherence, quality of life, and laboratory tests that include erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) at baseline and after 6 months. After 6 months, a significant difference in DRPs, Morisky medication adherence scale (MMAS-8), number of adverse drug reactions, and administration errors were noted between the intervention and control groups. A significant reduction was observed in disease activity score 28 (DAS28), health assessment questionnaire (HAQ), RA quality of life (RAQoL) score, ESR, and CRP in the intervention group when compared to the control group. In conclusion, the introduction of pharmaceutical care services in RA patient treatment protocol effectively resulted in an improvement in the detection and prevention of drug-related problems. Moreover, these professional pharmaceutical practices showed a significant reduction in DAS28, HAQ, RAQoL scores indicating a decrease in disease activity, and functional disability with an improvement in patient adherence and quality of life. Clinical trial registration: ClinicalTrials.gov identifier: NCT03743181.